Patterns of Risky Behaviors Associated with Methamphetamine Use Among Young Thai Adults: A Latent Class Analysis - Susan G. Sherman (2018)
Purpose: Methamphetamine (MA) is the leading illicit drug in Thailand among youth and young adults. Sexual risk behaviors are associated with methamphetamine use, but few data are available on the daily context of methamphetamine use. We developed an inductive behavioral typology that young Thais engage in while using methamphetamine. Methods: We conducted a cross-sectional study in Chiang Mai, Thailand, in 2005-2006 among 1,162 street-recruited methamphetamine smokers 18-25 years of age. Data collected included sociodemographic characteristics, sexual behaviors, and drug use patterns. Latent class analysis was used to describe patterns of activities in which participants reported engaging directly after using MA. Logistic regression was used to examine univariate correlates of class membership, separately by gender. Results: Participants were 75% male with a median age of 19 years. More than half of participants reported frequent alcohol use (≥4 days/week) and half of the sample reported smoking MA ≥2 days/ week. Three classes of activities emerged for male participants (n = 863): "work" (job related); "high-risk behaviors" (motorcycle riding, fighting, sex); and "combined" (all activities). Two classes emerged for the women (n = 299): "work" (housework) and "high-risk behaviors." "High-risk behaviors" and "combined" (men only) classes were associated with more frequent alcohol and methamphetamine use compared with the "work" class. Conclusions: Our study found a distinct typology of behaviors associated with substance abuse among young adults in Thailand. Behavioral typologies allow a better understanding of the nuances of "risky" behaviors and might prove useful in targeting interventions. © 2009 Society for Adolescent Medicine.